Effects of mental fatigue on Olympic ball sports performance: a systematic review - Pan, Xiaoyang; Soh, Kim Geok; Wan Jaafar, Wan Marzuki; Soh, Kim Lam; Li, Mingtian; Liu, Huange; Liu, Cong (Elsevier, 2025)
Ball sports differ from Olympic events such as athletics, gymnastics, and diving due to their dynamic and unpredictable environments, real-time changing tasks, and complex object manipulation. Mental fatigue due to cognitive load is almost inevitable. This review searched PubMed, Web of Science, SPORTDiscus, and Scopus, including 23 articles and analyzing 10 Olympic ball sports. Results indicate that mental fatigue negatively impacts various aspects of ball sport athletes' performance, including psychological, cognitive, decision-making, physical, and specific skill performance. Among the studied sports, soccer and basketball have the highest number of studies. However, research on other globally popular sports, such as rugby and golf, remains limited, and many Olympic ball sports still lack relevant studies, highlighting gaps in the research. In certain ball sports, physical performance, specific skill performance, and decision-making time did not significantly decline under mental fatigue. This could be attributed to differences in athletes' cognitive resource reserves, cognitive load tolerance, recovery ability, and psychological resilience. Due to differences in competition environments and task demands across ball sports (such as basketball vs. golf), the patterns of mental fatigue may vary, posing challenges in formulating a universal intervention strategy for mental fatigue recovery. Furthermore, most existing studies induce mental fatigue using laboratory tasks, which may not adequately simulate real competition scenarios. Future research should consider field data collection or using actual competitions as an intervention to induce mental fatigue.